U-Pb ages of syndeformational dykes associated with the Mesoproterozoic Nain Plutonic Suite, Labrador - Cadman, Andrew C; Noble, Steve R; Tarney, John; Park, R Graham; Ryan, A Bruce; Royse, Kate R (Canadian Journal of Earth Sciences, 1999)
Field and U-Pb zircon geochronological studies in a suite of crosscutting, deformed, and metamorphosed basic dykes show that they were emplaced in a syndeformational environment between 1328 ± 2 and 1316.5 ± 1.6 Ma. Earlier dykes in the suite are granulitic, commonly folded along north-south axes or strongly rotated into north-south-trending shear zones. Later dykes are metamorphosed to amphibolite grade. These sometimes retain igneous porphyritic textures and occasionally crosscut the granulite dykes. The amphibolite dykes were emplaced in a less ductile crustal environment and a structural environment less dominated by shear deformation. Both granulitic and to a lesser extent amphibolite dykes show evidence of synshear emplacement. The episode of emplacement is broadly coeval with the injection of the mid-Proterozoic Nain Plutonic Suite (NPS) and suggests that the dykes were injected as a series of leaks from NPS feeder chambers. If so, the granulite dykes may represent leaks intruded near the culmination of NPS activity, whereas the amphibolite dykes were probably injected during the waning phase of tectono-thermal conditions.